(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Chronotherapy has been emerging as a novel technology in the field of pharmaceutical research. Delivery of drugs with respect to the circadian rhythm has gained greater importance in the diseases such as diabetes, asthma and hypertension in producing maximum therapeutic action. Present study focus on the formulation and evaluation of Nimodipine pulsatile release tablets with the incorporation of Eudragit pH sensitive polymers used for the chronotherapy of hypertension. Pharmacologically Nimodipine is an anti-hypertensive agent that acts by blocking the L and N-type calcium channels. Evaluation parameters for Nimodipine tablets included friability, drug content, bulk and tapped density, angle of repose and Carr’s index and drug release in vitro and in vivo.